ANALISIS YURIDIS PARAMETER PEMBELAAN TERPAKSA (NOODWEER) DALAM KUHP LAMA DAN UU NOMOR 1 TAHUN 2023 - Ika Febriana; Ibrahim Fikma Edrisy (CV. Denasya Smart Publisher, 2026)
The purpose of this study is to analyze the legal parameters of forced defense (noodweer) and forced defense beyond the limit (noodweer exces) in the transition of criminal law from the old Criminal Code (Wetboek van Strafreth) to Law Number 1 of 2023. The research method used in this study is normative juridical statutory and conceptual approach. the replacement of the Old Criminal Code (Wetboek van Strafreth), Law Number 1 of 2023 provides systematic clarity with a clear separation between justification and excuse reasons in forced defense (noodweer). However, in practice, in practice, the defense of self-defense is often rejected due to fraud to prove the immediate element in the attack incident, and there is a failure to show a causal relationship in the attack on the grounds of